2018
DOI: 10.1038/s41417-018-0045-y
|View full text |Cite
|
Sign up to set email alerts
|

GINS2 promotes cell proliferation and inhibits cell apoptosis in thyroid cancer by regulating CITED2 and LOXL2

Abstract: To explore the mechanisms of GINS2 on cell proliferation and apoptosis in thyroid cancer (TC) cells. Expressions of GINS2 were inhibited in K1 and SW579 cells using gene interference technology. The abilities of proliferation and apoptosis, and cell cycle were determined by MTT assay and flow cytometric assay. The downstream molecules of GINS2 were searched by microarray and bioinformatics and validated by qRT-PCR and western blotting. In the in vivo study, the tumor growth was compared and the whole-body fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…LOXL2 is a member of the LOX gene family, which encodes a copper-dependent amine oxidase that catalyzes the first step in the formation of crosslinks in collagens and elastin (49,50). It is involved in the progression of tumor progression and metastasis (31,49,(51)(52)(53). Upregulated expression of LOXL2 has been revealed in several types of cancer, including HCC (54).…”
Section: Discussionmentioning
confidence: 99%
“…LOXL2 is a member of the LOX gene family, which encodes a copper-dependent amine oxidase that catalyzes the first step in the formation of crosslinks in collagens and elastin (49,50). It is involved in the progression of tumor progression and metastasis (31,49,(51)(52)(53). Upregulated expression of LOXL2 has been revealed in several types of cancer, including HCC (54).…”
Section: Discussionmentioning
confidence: 99%
“…By interrogating GSE37815 data series from GEO database, we found that GINS2 was among the top 5 most DEGs with a log2FC=1.99 and adjusted P value=0.00462. Like TRPM2-AS, we found that GINS2 was considered to be a significant tumor promoter in thyroid cancer [32] lung cancer [33], cervical cancer [40], ovarian cancer [38], breast cancer [34], triple-negative breast cancer [35], and leukemia [39]. Based on these findings, we thus hypothesized that GINS2 might be a tumor promoter in BLCA as well.…”
Section: The Identification Of Genes Of Interest In This Studymentioning
confidence: 73%
“…GINS2 has been preliminarily studied in various human cancers such as that GINS2 enhanced cell proliferation and weakened cell apoptosis in thyroid cancer by regulating CITED2 and LOXL2 expression [32]. GINS2 was upregulated in NSCLC tissues and cell lines, indicating with the poor prognosis outcome of the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since GINS2 mediates the initiation of DNA replication in eukaryotic cells, which is essential for S-phase progression and cell division, GINS2 is more likely to participate in the regulation of cell cycle progression [26]. In addition, previous studies indicated that Cyclin D1 is a key protein in cell cycle regulation [27][28][29].…”
Section: Discussionmentioning
confidence: 99%